Contrast-enhanced ultrasound findings of gallbladder adenocarcinoma with sarcomatoid carcinoma accompanied by intrahepatic metastasis: A case report and literature review. Issue 21 (May 2018) - Wang, Hong; Ling, Wenwu; Luo, Yan
Abstract: Rationale: Gallbladder adenocarcinoma is the most common subtype of malignant tumor in gallbladder carcinoma; its incidence is quite low. Preoperative diagnosis of gallbladder adenocarcinoma appears to be very difficult because they are normally asymptomatic and are often found incidentally. Adenocarcinoma with sarcomatoid carcinoma of gallbladder is exceedingly rare with no case reported in the literature to date. Patient concerns: A 69-year-old male was referred to our hospital due to right upper quadrant pain. To further diagnosis, he received laboratory tests, gray-scale US, and contrast-enhanced ultrasound (CEUS). In this present study, ethical approval was not necessary, as this article is a case report, which is based on the clinical information of the patient. The patient gave his permission for publication of the case. Diagnoses: Gray-scale abdominal ultrasound image demonstrated a hypoechoic intraluminal mass of gallbladder and a heterogeneous mass at the inferior segment of the right anterior liver lobe. In CEUS, the lesion of gallbladder was hyper-enhanced in the arterial phase, and hypo-enhanced in the later arterial phase. On liver, the hepatic lesion appeared heterogenous mild enhancement in the arterial phase. In portal and parenchymal phase, the hepatic lesion displayed hypo-enhancement, which conformed to the hepatic metastasis. Interventions: The patient received cholecystectomy, right hepatectomy, and lymphadenectomy. Outcomes: He had an uneventful recovery from the procedure. Lessons: We presented a case report with gallbladder adenocarcinoma with sarcomatoid carcinoma accompanied by intrahepatic metastasis, focusing on the ultrasound imaging features of this tumor, especially its enhancement pattern on CEUS. CEUS provided helpful information for diagnosis. Herein, we report the case; and the associated literature is further reviewed.